Efficacy, safety, and feasibility of volumetric modulated arc therapy for synchronous bilateral breast cancer management - Quesada, Stanislas; Fenoglietto, Pascal; Gourgou, Sophie; Lemanski, Claire; Draghici, Roxana; Ailleres, Norbert; Prunaretty, Jessica; Azria, David; Bourgier, Céline (Frontiers in Oncology, 2022)
Purpose: Volumetric Modulated Arc Therapy (VMAT) exhibits potent advantages regarding target volume coverage and protection of organs at risk, notably in the context of anatomical constraints. Nevertheless, reports concerning VMAT for the treatment of synchronous bilateral breast cancers (SBBC) have been scarce to date. As such, we conducted this observational study to assess efficacy, safety and feasibility of VMAT in SBBC. Materials and Methods: from August 2011 to December 2017, 54 consecutive patients with SBBC with or without axillary nodes involvement underwent a treatment protocol containing radiotherapy using VMAT. A total dose (TD) of 52.2Gy in 29 fractions was delivered to breast and internal mammary chain (IMC) nodes Planning Target Volume (PTV) plus, if applicable, a TD of 49.3Gy in 29 fractions to the supra- and infra-clavicular nodes PTV and a TD of 63.22Gy in 29 fractions to tumor boost PTV. Lungs, heart, esophagus, trachea, liver, thyroid and spinal cord were considered as organs at risk. VMAT feasibility and organ at risk sparing were evaluated by treatments planning of the 20 first enrolled patients. Tolerance and patients’ outcome were prospectively monitored by acute/late toxicities records and by the analysis of overall survival (OS), locoregional recurrence-free survival (LRFS) and recurrence-free survival (RFS). Results: breast, supraclavicular nodes and boost PTV coverage was adequate with at least 98% of PTV encompassed by more than 95% of the prescribed dose. Less than 90% of IMC PTV was encompassed by 95% of the prescribed dose. Mean lung dose was 12.3Gy (range: 7.7 – 18.7); mean heart dose was 10.7Gy (range: 6.2 – 22.3). Concerning acute toxicities, only 2 patients experienced grade 3 skin toxicity (3.7%) and only 1 patient developed grade 1 pneumonitis. After a median follow-up of 5.3 years, grade 2 fibrosis and/or shrinking was observed in 5 patients (10%), and grade 3 fibrosis in 1 patients (2%). The 5-year LRFS-rate, RFS-rate and OS were 98% [95% CI= 86.12-99.70%], 96% [95% CI= 84.63-98.96%] and 100%, respectively.